EFEK PEMBERIAN TEPUNG DAUN PEPAYA (Carica Papaya) TERHADAP PERFORMA PRODUKSI PUYUH (Coturnix Coturnix Japonica) - Exzel Overmarz Mulkay; David Kermite; Muhammad Juraid Watiheluw (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to evaluate the effect of adding papaya leaf flour (Carica papaya L.) to feed on the production performance and egg weight of Japanese quail (Coturnix coturnix japonica). The research employed a Completely Randomized Design (CRD) with four treatments, each repeated twice. The parameters analyzed included feed consumption, feed conversion efficiency, the number of eggs produced, and egg weight. The results indicated that supplementing feed with papaya leaf flour at levels of 3% to 6% could enhance feed conversion efficiency to an optimal level. The DP2 treatment yielded the best results, with the lowest feed conversion ratio of 4.67, reflecting the highest feed efficiency. These findings suggest that papaya leaf flour has the potential to serve as a natural feed supplement that can improve egg production efficiency in Japanese quail.